DIPLOMASI BUDAYA INDONESIA TERHADAP BELGIA MELALUI EUROPALIA 2017 - Zia Aurani; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This paper aims to analyze cultural diplomacy that explains Indonesia’s participation in the Europalia festival in Belgium. Cultural diplomacy is a category of soft diplomacy in the implementation of a country’s foreign policy. Cultural instruments used by Indonesia in the implementation of diplomacy through Europalia can refclet the identity of the Indonesian state namely Bhineka Tunggal Ika.This study uses constructivist perspectives by Alexander Wendt, the analysis unit of the nation state and uses the theory of diplomacy by S.L Roy, and supported by the concept of multitrack diplomacy by Louise Diamond and John W McDonald's uses track 1 (Government), track 2 (Actor non-government) and track 9 (Media). And then the concept of cultural diplomacy by Tulus Warsito dan Wahyuni Kartikasari.The research shows that the Indonesian Europalia festival stole the attention of many Belgian and European citizens. Seen from the number of visitors or viewers who reached thousands of people at the festival. Increased knowledge and interest in Indonesian culture can attract Belgian citizens to visit Indonesia. Indonesian cultural diplomacy at the Europalia festival cam convey cultural values well. So that the cooperative relationship between Indonesia and Belgium can continue to increase. It’s not only in one field, but in several other fields.Keywords: Cultural Diplomacy, Europalia, Constructivist Perspectives, Diplomacy Theory, Multi-track Diplomacy